Discover a wealth of knowledge at Westonci.ca, where experts provide answers to your most pressing questions. Our platform provides a seamless experience for finding precise answers from a network of experienced professionals. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
Answer:
Is (-5/6)*x = 6? Then x = -36/5.
Is (-5/6x) = 6? Then x = -5/36.
Step-by-step explanation:
I hate to nitpick, but the question itself leaves a lot up to interpetation thanks to PEMDAS. In math, it matters if numbers and variables are either in the numerator or the denominator of a fraction. If the arrangement is made unclear, then differing answers may appear, and that's not a really good look for mathematics as a whole. But since I'm nice, I'll answer the two equations that this question can be interpeted as.
First intepretation: (-5/6)*x = 6
The only step we do is multiply both sides by (-6/5) to get x by itself. Remember that when you multiply a number by its reciprocal, the product is 1. So, if we multiply (-5/6) by its reciprocal (-6/5), it equals 1. They then cancel out.
(-5/6)*x = 6
(-6/5)*(-5/6)*x = 6*(-6/5)
x = -36/5
Second Interpretation: (-5/6x) = 6
Since x is in the denominator, we need to get it out of there so our answer equals x and not 1/x. So, we will multiply both sides by x.
(-5/6x) = 6
x*(-5/6x) = x*6
-5/6 = 6x
Then, we divide 6 on both sides to isolate x.
(-5/6)/6 = (6x)/6
-5/36 = x
x = -5/36
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.